Study of Sorption Kinetics and Sorption–Desorption Models to Assess the Transport Mechanisms of 2,4-Dichlorophenoxyacetic Acid on Volcanic Soils - Escudey-Castro, A; Escudey-Castro, A (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
The sorption behavior of 2,4-dichlorophenoxyacetic acid (2,4-D) in the abundant agricultural volcanic ash-derived soils (VADS) is not well understood despite being widely used throughout the world, causing effects to the environment and human health. The environmental behavior and risk assessment of groundwater pollution by pesticides can be evaluated through kinetic models. This study evaluated the sorption kinetics and 2,4-D sorption–desorption in ten VADS through batch sorption experiments. Differences in the sorption extent for the fast and slow phases was observed through the IPD model where 2,4-D sorption kinetics was controlled by external mass transfer and intra organic matter diffusion in Andisols (C1 ̸≠ 0). We confirmed from the spectroscopic analysis that the carboxylate group directly drives the interaction of 2,4-D on Andisol soil. The MLR model showed that I EP, FeDCB, and pH × Silt are important soil descriptors in the 2,4-D sorption in VADS. The Freundlich model accurately represented sorption equilibrium data in all cases (Kf values between 1.1 and 24.1 µg1−1/n mL1/n g−1 ) with comparatively higher sorption capacity on Andisols, where the highest hysteresis was observed in soils that presented the highest and lowest OC content (H close to 0). © 2021 by the authors. Licensee MDPI, Basel, Switzerland.